(untitled) (Research, Society and Development, 2023)
Spin-Off comes from the English word that means derivation, applied in the business environment, several studies present that the use of Spin-Off as essential to the culture of innovation. The purpose of this research is to study the Spin-Off, understanding the aspects related to the strategies of managers. To this end, bibliographic research, articles will be raised. As well as a case study in the company in the sector Esmalteria to verify the process of adapting the consolidated business model for Spin-Off thus leveraging the company’s brand. The result found was the strategy of taking advantage of the new opportunity in the expansion of segmentation, which consequently led them to new challenges, stable profitability and beyond that of an innovation-oriented company.